Effect of Glycine on Lead Mobilization, Lead-Induced Oxidative Stress, and Hepatic Toxicity in Rats - Alcaraz Contreras, Yolanda; Garza Ocañas, Lourdes; Carcaño Díaz, Katya; Ramírez Gómez, Xóchitl Sofía (2011)
The effectiveness of glycine in treating experimental lead intoxication was examined in rats. Male Wistar rats were exposed to 3 g/L lead acetate in drinking water for 5 weeks and treated thereafter with glycine (100 and 500 mg/kg, orally) once daily for 5 days or glycine (1000 mg/kg, orally) once daily for 28 days. The effect of these treatments on parameters indicative of oxidative stress (glutathione and malondialdehyde levels), the activity of blood δ-aminolevulinic acid dehydratase, and lead concentration in blood, liver, kidney, brain, and bone were investigated. Liver samples were observed for histopathological changes. Glycine was found to be effective in (1) increasing glutathione levels; (2) reducing malondialdehyde levels; (3) decreasing lead levels in bone with the highest dose. However, glycine had no effect on lead mobilization when 100 and 500 mg/kg glycine were administered. In microscopic examination, glycine showed a protective effect against lead intoxication.